[Conference report] Indigenous Identity in Demography - Axelsson, Per (Journal of Northern Studies, 2007)
The Centre for Sami Research (CeSam) and the Centre for Population Studies (CPS) at Umeå University hosted the workshop Indigenous Identity in Demographic Sources, in September 29–30, 2006. The theme brought together 35 researchers from the circumpolar north and beyond.